2011
DOI: 10.1021/bm201588m
|View full text |Cite
|
Sign up to set email alerts
|

Triply Triggered Doxorubicin Release From Supramolecular Nanocontainers

Abstract: The synthesis of a supramolecular double hydrophilic block copolymer (DHBC) held together by cucurbit[8]uril (CB[8]) ternary complexation and its subsequent self-assembly into micelles is described. This system is responsive to multiple external triggers including temperature, pH and the addition of a competitive guest. The supramolecular block copolymer assembly consists of poly(N-isopropylacrylamide) (PNIPAAm) as a thermoresponsive block and poly(dimethylaminoethylmethacrylate) (PDMAEMA) as a pH-responsive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(118 citation statements)
references
References 42 publications
1
117
0
Order By: Relevance
“…[42][43][44][45] For instance, Lee and Scherman et al have demonstrated the release of cancer drugs from hierarchical nanocarriers can be controlled by three orthogonal, biologically relevant triggers (pH, temperature and a specific molecular cue) that can result in disassembly of the micelles, releasing doxorubicin. 46 This controlled release reduces toxicity to other areas of the body. A wide range of stimuli-responsive polymeric structures have been designed, governed by hydrophobic interactions, which can selectively release molecules in response to certain stimuli.…”
Section: Self-assembled Nanomachinesmentioning
confidence: 99%
“…[42][43][44][45] For instance, Lee and Scherman et al have demonstrated the release of cancer drugs from hierarchical nanocarriers can be controlled by three orthogonal, biologically relevant triggers (pH, temperature and a specific molecular cue) that can result in disassembly of the micelles, releasing doxorubicin. 46 This controlled release reduces toxicity to other areas of the body. A wide range of stimuli-responsive polymeric structures have been designed, governed by hydrophobic interactions, which can selectively release molecules in response to certain stimuli.…”
Section: Self-assembled Nanomachinesmentioning
confidence: 99%
“…The macrocyclic host, cucurbit [7]uril (CB [7]) was chosen as the model. Cucurbit[n]urils (CB[n]s) are a family of water-soluble macrocyclic hosts, which have a hydrophobic cavity capable of the binding of one or two guest molecules depending on the size of di®erent CB[n]s. [22][23][24] CB [7] possesses good solubility in water and strong a±nity for one guest molecule. [25][26][27][28][29][30][31] The authors employed CB [7] to bind with the positive charge and hydrophobic component on "-poly-l-lysine hydrochlorides to construct the polypseudorotaxane for antibacterial regulation.…”
Section: Responsive Antibacterial Materialsmentioning
confidence: 99%
“…The final product was dialyzed against deionized water through dialysis tube (M w cutoff: 8000-14,000 g mol 21 ) for 1 week to remove the unreacted mPEG (see Supporting Information Fig. S5).…”
Section: Synthesis Of 4-adamantane Carboxylate Benzaldehydementioning
confidence: 99%